Asas Akuntabilitas dalam Perkara Tindak Pidana Korupsi Anggota Parlemen di Indonesia - Titan Triatna Kurniawan; Suwari Akhmaddhian (Universitas Kuningan, 2019)
The purpose of this study is to determine the principle of accountability plays an important role for the formation of good governance (Good Government) and to know the form of good governance can play an important role for the formation of accountability. The research method used by the author is Normative Juridical, with data collection tools through literature study. The results of the study showed that Good Governance or good governance wherein the thought originated that the management of public administration is the main issue in achieving towards